London Quakers in the trans-atlantic world the creation of an early modern community - Landes, Jordan 1972- (Basingstoke New York Palgrave Macmillan, 2015)
Quaker institutional structures -- Communicating religion with friends "beyond the seas" -- Communicating politics with friends "beyond the seas" -- Quaker merchants and transatlantic commercial activity in London -- The transatlantic Quaker book trade -- Movement of people in the Quaker Atlantic -- Colonial perceptions
Quaker institutional structuresCommunicating religion with friends "beyond the seas" -- Communicating politics with friends "beyond the seas" -- Quaker merchants and transatlantic commercial activity in London -- The transatlantic Quaker book trade -- Movement of people in the Quaker Atlantic -- Colonial perceptions.
Includes bibliographical references
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Quakers -- England -- London -- History -- 17th century; Society of Friends -- England -- London -- History -- 17th century; Quakers -- History -- 17th century -- England -- London; Society of Friends -- History -- 17th century -- England -- London; British colonies; Commerce; Manners and customs; Quakers; Society of Friends; London (England) -- Social life and customs -- 17th century; London (England) -- Commerce -- History -- 17th century; Great Britain -- Colonies -- Commerce -- History -- 17th century; London (England) -- Social life and customs -- 17th century; London (England) -- Commerce -- History -- 17th century; Great Britain -- Colonies -- Commerce -- History -- 17th century -- England -- London -- History